2010
DOI: 10.1111/j.1364-3703.2009.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

The hypersensitive response induced by the V2 protein of a monopartite begomovirus is countered by the C2 protein

Abstract: A functional analysis of the V2 protein of two monopartite begomoviruses, Papaya leaf curl virus (PaLCuV) and Cotton leaf curl Kokhran virus (CLCuKoV), has been performed. Expression of the V2 gene from a Potato virus X (PVX) vector resulted in severe leaf curling followed by a hypersensitive response (HR) in Nicotiana benthamiana and N. tabacum, demonstrating that the V2 protein is a pathogenicity determinant and a target of host defence responses. Agroinfiltration of a PVX vector expressing the V2 protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 54 publications
(103 reference statements)
1
64
0
Order By: Relevance
“…The PVX expression system was shown to be productive for the expression of various begomovirus individual genes in N. benthamiana and tomato plants (Hussain et al 2007;Mubin et al 2010;Sharma and Ikegami 2010;Luna et al 2012). The recombinant PVX was infiltrated into N. benthamiana and tomato leaves, and the treated plants were maintained in a greenhouse for 30 days, during which symptoms were periodically recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVX expression system was shown to be productive for the expression of various begomovirus individual genes in N. benthamiana and tomato plants (Hussain et al 2007;Mubin et al 2010;Sharma and Ikegami 2010;Luna et al 2012). The recombinant PVX was infiltrated into N. benthamiana and tomato leaves, and the treated plants were maintained in a greenhouse for 30 days, during which symptoms were periodically recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the ToLCNDV-encoded genes pointed to the transcriptional activator protein (TrAP) (encoded by DNA A) as the factor mediating the anti-HR effect (Hussain et al 2005). Later on, the V2 protein of two monopartite begomoviruses, Papaya leaf curl virus (PaLCuV) and Cotton leaf curl Kokhran virus (CLCuKoV), was shown to be a pathogenicity determinant and a target of host defense responses in N. benthamiana and N. tabacum plants (Mubin et al 2010). C2/TrAP protein of PaLCuV or Cotton leaf curl Multan virus inhibited the HR induced by V2 in the virus-agroinfiltrated areas.…”
Section: Introductionmentioning
confidence: 99%
“…controls viral induced hypersensitive cell death (Hussain et al, 2007;Mubin et al, 2010), AC3 Replication enhancer protein (REn)…”
Section: Ac2 Transcription Associated Protein (Trap)mentioning
confidence: 99%
“…For example Stanley and Latham [58] have shown that V2 protein of Papaya leaf curl virus (PaLCuV) is potentially involved in the elicitation of cell death response. The deletion mutants (having deletions of 32 and 60 amino acids, respectively, at the N-terminal end of V2) exhibited a systemic HR in Nicotiana benthamiana plants.…”
Section: Mutated Orf Mutation Position Type Of Mutationmentioning
confidence: 99%
“…Phosphorylation of MPs may also play a role in controlling the switch from viral replication to translation [36,37]. Few earlier studies showed that for PaLCuV V2, deletion of sequences encompassing this motif abrogates the ability to induce HR [58].…”
Section: Mutated Orf Mutation Position Type Of Mutationmentioning
confidence: 99%